Perancangan Game Edukasi Pengenalan Lagu Wajib Pada Siswa SD Menggunakan Metode CBI Berbasis Android - Amelia Siregar; Herlina Harahap; Nenna Irsa Syahputri (SNASTIKOM, 2023)
The development of technology is now growing rapidly so that it has a varied impact. Including a positive impact, where now there are many effective and interesting learning media that can be accessed only through smartphones. Educational games are a tool used in introducing national compulsory songs to elementary school children. There are many national compulsory songs and each song contains different meanings, both in the form of celebrating the services of heroes and in fostering the spirit and love of the motherland. In this study, the game was designed based on Android, because it can be accessed and used anytime and anywhere. The method used in designing this application is the Computer based Instruction (CBI) method where this method aims to increase children's interest in learning and can be a substitute medium for books in learning. Because the Computer Based Instruction (CBI) method is a learning method that is instructed by computers as a whole. The results of this study show that the compulsory song recognition educational game for elementary school students using the Android-based Computer Based Instrument method is worthy as an interesting and influential introduction and learning medium for elementary school students.